Rare Carwash / Mohd Azlan Sulaiman ... [et al.] - Sulaiman, Mohd Azlan; Kelana, Mohammad Khairuddin; Md Tajudin, Muhd Arif Akmal; Olui, Raymond; Junion Menggoyo, Sarah (2016)
RARE CARWASH is a unique carwash service. It is unique in the way that the business itself will go to where the customers are. In other words, we offer door-to-door carwash service for customers and they can get our service just by giving us a call. We expect our customers to mostly consist of people in KKIP Sepanggar who are working and having a busy schedule. In order to attract customers and to make the people in KKIP Sepanggar aware of the existence of our business, we put out ads in newspaper, hang banners and make a business account on social media as advertising. For customers have already use our service, we will also hand out free stickers for them to put on their cars so this will create higher opportunities for outsiders to know about our business. We also provide sales promotion to increase the opportunity of obtaining more customers. When compared to the competitors, we have an advantage in this business because even though we are doing the same business, our concept is not the same. For other competitor, they are operating at a fixed place. This means that the customers have to go out of the comfort of their home in order to get a carwash service. Unlike our service as we have mentioned before, the customers can simply call us to enjoy our service without leaving their home. The customers can relax while waiting for us to finish washing their car at their home. As a conclusion, our company provide a very convenient and time-saving service for the customers, therefore we believe that this business will be profitable and have a high probability to expand in the future.